Fostering student engagement with criticism feedback: importance, contrasting perspectives and key provisions - Rabbani, Lutfieh M.; Husain, Salwa Habib (Frontiers in Education, 2024)
Criticism, or critical feedback, is considered rich bits of information about the student's weaknesses, thinking, and learning. Despite its importance as part of formative assessment processes, this type of feedback is especially challenging for teachers to communicate as well as for students to uptake. The current conceptual analysis therefore highlights the substantial role that criticism plays in advancing students' learning and progress. It presents a wide range of contrasting perspectives toward criticism to show how it is perceived differently. Lastly, the article identifies key provisions that are necessary for critical feedback to be constructed, presented, interpreted, and utilized in constructive and nonthreatening ways, which subsequently help trigger learner's positive reactions and engagement with the received information. These provisions help create a community of practice where objective, informative, transparent, and engaging criticism can be given, respected, negotiated, and benefited from. The implications of these provisions for practice are discussed.